THE IMPACT OF TIKTOK SOCIAL MEDIA ON THE RELIGIOUSNESS OF HIGH SCHOOL TEENAGERS - Agustine, Fatimatuz Zahro (UIN Sunan Kalijaga Yogyakarta, 2025)
TikTok has become one of the most popular digital platforms among teenagers, including secondary school students, due to its ease of access, content creation, and entertainment sharing features. However, uncontrolled intensity of TikTok use can affect various aspects of teenagers’ lives, including their religiosity. Based on this phenomenon, this study was conducted under the title “The Influence of TikTok Usage Intensity on the Religiosity of Secondary School Teenagers.” The objectives of this research are to: (1) describe the intensity of TikTok use among secondary school teenagers, (2) describe the level of religiosity among secondary school teenagers, and (3) determine the influence of TikTok usage intensity on the religiosity of secondary school teenagers. This study employed a descriptive quantitative approach. The population consisted of 284 eleventh-grade students, with a purposive sampling technique used to select 75 respondents. The research instrument consisted of a questionnaire with 15 items for the TikTok usage intensity variable and 27 items for the religiosity variable, supported by interview and documentation data. Data were analyzed using descriptive statistics for quantitative data and descriptive analysis for qualitative data. The findings indicate a significant influence between TikTok usage intensity and the religiosity of secondary school teenagers. The coefficient of determination (R Square) was 0.212, indicating that TikTok usage intensity contributed 21.2% to religiosity, while the remaining 78.8% was influenced by other factors. Interviews with teachers and students reinforced the finding that TikTok content can have both positive and negative impacts on teenagers’ religious awareness and practices. Keyword: Social Media, TikTok, Religiosity, Teenagers, Secondary School Media sosial TikTok menjadi salah satu platform digital yang sangat digemari oleh remaja, termasuk siswa SMA, karena kemudahannya dalam mengakses, membuat, dan membagikan konten hiburan. Namun, penggunaan TikTok yang tidak terkontrol dapat memengaruhi berbagai aspek kehidupan siswa, termasuk dalam hal perilaku keagamaan. Berdasarkan fenomena tersebut, penelitian ini dilakukan dengan judul “Pengaruh Penggunaan TikTok terhadap Perilaku Keagamaan Siswa SMAN 4 Pasuruan.” Tujuan penelitian ini adalah untuk: (1) mendeskripsikan penggunaan TikTok oleh siswa SMAN 4 Pasuruan, (2) mendeskripsikan perilaku keagamaan siswa SMAN 4 Pasuruan, dan (3) mengetahui pengaruh penggunaan TikTok terhadap perilaku keagamaan siswa. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Populasi dalam penelitian berjumlah 284 siswa kelas XI, dan pengambilan sampel menggunakan teknik purposive sampling sebanyak 75 siswa. Instrumen penelitian berupa angket dengan 15 butir untuk variabel penggunaan TikTok dan 27 butir untuk variabel perilaku keagamaan, serta didukung data wawancara dan dokumentasi. Metode analisis yang digunakan adalah analisis statistik deskriptif untuk penelitian yang bersifat kuantitatif dan analisis hipotesis deskriptif untuk penelitian yang bersifat kualitatif. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan antara penggunaan TikTok dan perilaku keagamaan siswa SMAN 4 Pasuruan. Nilai koefisien determinasi (R Square) sebesar 0,212, yang berarti penggunaan TikTok memberikan kontribusi sebesar 21,2% terhadap perilaku keagamaan siswa, sedangkan sisanya 78,8% dipengaruhi oleh faktor lain. Hasil wawancara dengan guru dan siswa memperkuat temuan bahwa konten TikTok dapat memberikan dampak positif maupun negatif terhadap kesadaran dan praktik keberagamaan siswa. Kata kunci: TikTok; Perilaku Keagamaan; Remaja; Media Sosial